Teachers' Perspectives on the Effectiveness of the Merdeka Curriculum - Septiyanisa Sekar Nawangwulan; I'tamaro Billahil Izzah; Kishi Ananta Tabita Rahma; Wirda Farfaza Nabila Rusafi; Candra Syifa’ul Mustofa (Pro-ELLitera, 2025)
This research was done on teachers' perceptions of the Merdeka Curriculum regarding its effectiveness, challenges, and how it can be improved. This research applied a qualitative descriptive approach to data collection through semi-structured interviews, focus groups, and document analysis. The findings reveal that teachers welcome the freedom of the curriculum to ensure students' creative thinking, critical thinking, and collaboration are developed. However, ineffective implementation of these aspects is faced by some challenges such as lack of adequate training and resource limitations, coupled with inequality in school readiness. This study, therefore, calls for continuous professional development, collaboration of stakeholders, and systemic reforms to heighten the success of the curriculum. These insights are expected to help policymakers and educators in improving the implementation of the Merdeka Curriculum for the development of a competent and character-driven generation.